Triethylamine-mediated protonation–deprotonation unlocks dual-drug self assembly to suppress breast cancer progression and metastasis - Lei Lei; Yujun Song; Lianyi Yang; Yazhen Wang; Xue Xia; Yiwei Zhang; Xiaoxian Zhang; Xuequan Zhang; Ishaan Duggal; Bin He; Nicholas A. Peppas; Jun Cao; et al. (Proceedings of the National Academy of Sciences, 2025)
Carrier-free nanomedicines exhibited significant potential in elevating drug efficacy and safety for tumor management, yet their self assembly typically relied on chemical modifications of drugs or the incorporation of surfactants, thereby compromising the drug’s inherent pharmacological activity. To address this challenge, we proposed a triethylamine (TEA)-mediated protonation–deprotonation strategy that enabled the adjustable-proportion self assembly of dual drugs without chemical modification, achieving nearly 100% drug loading capacity. Molecular dynamic simulations, supported by experiment evidence, elucidated the underlying self-assembly mechanism. Specifically, TEA facilitated the deprotonation of Doxorubicin (Dox) and α-Tocopherol succinate (α-tos), causing Dox to transition from a hydrophilic to a hydrophobic state, while simultaneously increasing the hydrophilicity of α-tos. This allowed for a fine-tuned balance between the hydrophilic and hydrophobic properties of the two compounds, enabling their precise self assembly into a carrier-free nanomedicine (DT) with a tailored drug ratio. The engineered DT demonstrated the ability to accumulate at the tumor sites and release its therapeutic drugs in a controlled manner. The combination of Dox and α-tos synergistically generated reactive oxygen species and modulated the expression of tumor matrix metalloproteinase-9, leading to superior antitumor efficacy without significant metastasis, while maintaining excellent safety profiles. Our findings provided unique perspectives on the design of carrier-free nanomedicine for cancer therapy, thereby laying a solid foundation for its potential clinical translation.